Carbon-Based Perovskite Solar Cell - Luigi Vesce; Maurizio Stefanelli; Aldo Di Carlo (Materials Proceedings, 2023)
In a short period, Perovskite solar cell (PSC) technology gained high efficiency and broad attention because of its key enabling physical and morphological features. One of the main obstacles to the PSC industrialization and commercialization deals with the demonstration of stable devices by adopting low-cost and reliable materials and fabrication methods. In the n-i-p structure, the organic hole-transporting layer and the metal counter-electrodes are the main causes of instability and high cost. Here, we substituted these two elements with a low-temperature and low-cost carbon-based counter electrode.